2014
DOI: 10.1093/pcp/pcu078
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heterotetrameric Assembly of Potato ADP-Glucose Pyrophosphorylase Using Reverse Genetics

Abstract: ADP-glucose pyrophosphorylase (AGPase) is a key allosteric enzyme in plant starch biosynthesis. Plant AGPase is a heterotetrameric enzyme that consists of large (LS) and small subunits (SS), which are encoded by two different genes. Computational and experimental studies have revealed that the heterotetrameric assembly of AGPase is thermodynamically weak. Modeling studies followed by the mutagenesis of the LS of the potato AGPase identified a heterotetramer-deficient mutant, LS(R88A). To enhance heterotetramer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…ADPglc content was then estimated for the purified amyloplast fraction and total seed extract by performing the reverse AGPase reaction coupled with phosphoglucomutase and Glc-6-P dehydrogenase reactions as described previously (Seferoglu et al, 2014). The reaction was initiated by the addition of excess amounts of near homogenously pure potato AGPase and performed at 37°C for 20 min in reaction buffer containing 100 mM HEPES, pH 7, 5 mM dithiothreitol, 5 mM 3-phosphoglyceric acid, 10 mM MgCl 2 , 0.6 mM NAD + , 0.4 mg mL 21 bovine serum albumin, 0.5 units of Glc-6-P dehydrogenase, and 0.5 units of phosphoglucomutase.…”
Section: Measurement Of Adpglc Levelsmentioning
confidence: 99%
“…ADPglc content was then estimated for the purified amyloplast fraction and total seed extract by performing the reverse AGPase reaction coupled with phosphoglucomutase and Glc-6-P dehydrogenase reactions as described previously (Seferoglu et al, 2014). The reaction was initiated by the addition of excess amounts of near homogenously pure potato AGPase and performed at 37°C for 20 min in reaction buffer containing 100 mM HEPES, pH 7, 5 mM dithiothreitol, 5 mM 3-phosphoglyceric acid, 10 mM MgCl 2 , 0.6 mM NAD + , 0.4 mg mL 21 bovine serum albumin, 0.5 units of Glc-6-P dehydrogenase, and 0.5 units of phosphoglucomutase.…”
Section: Measurement Of Adpglc Levelsmentioning
confidence: 99%
“…The heterotetrameric assembly properties of the LS E370G mutant AGPase with wild type SS were investigated using 3-13% gradient native polyacrylamide gels followed by Western blot using potato anti-LS and anti-SS antibodies as previously described [27].…”
Section: Native Page Analysismentioning
confidence: 99%
“…Modeling studies followed by mutagenesis of the potato AGPase identified a hotspot mutant AGPase for the interaction of head to tail LS-SS dimers, where an Arg residue at position 88 was replaced by Ala in the LS (LS R88A ) [30,34]. In our previous study we employed an error prone-PCR random mutagenesis approach using the LS A88 AGPase cDNA as template to select second-site LS suppressor that could reverse the iodine staining deficiency of the E.coli glgCcontaining wild type SS AGPase cDNA [27].…”
Section: The Large Subunit E370g Mutation Impairs Glycogen Productionmentioning
confidence: 99%
See 2 more Smart Citations